Neighborhood built environment and physical activity of Japanese older adults: results from the Aichi Gerontological Evaluation Study (AGES) - Hirai Hiroshi; Nakaya Tomoki; Kawachi Ichiro; Hanibuchi Tomoya; Kondo Katsunori (BMC, 2011)
Abstract Background Although many studies have reported the association between neighborhood built environment (BE) and physical activity (PA), less is known about the associations for older populations or in countries besides the US and Australia. The aim of this paper is to examine the associations for older adult populations in Japan. Methods Our analyses were based on cross-sectional data from the Aichi Gerontological Evaluation Study (AGES), conducted in 2003. The respondents were older adults, aged 65 years or over (n = 9,414), from 8 municipalities across urban, suburban, and rural areas. The frequency of leisure time sports activity and total walking time were used as the outcome variables. Using geographic information systems (GIS), we measured residential density, street connectivity, number of local destinations, access to recreational spaces, and land slope of the respondents' neighborhoods, based on network distances with multiple radii (250 m, 500 m, 1,000 m). An ordinal logistic regression model was used to analyze the association between PA and BE measures. Results Population density and presence of parks or green spaces had positive associations with the frequency of sports activity, regardless of the selected buffer zone. The analysis of total walking time, however, showed only a few associations. Conclusions Our findings provide mixed support for the association between PA and the characteristics of BE measures, previously used in Western settings. Some characteristics of the neighborhood built environment may facilitate leisure time sports activity, but not increase the total walking time for Japanese older adults.